Effect of Viscosity Ratio of Two Immiscible Polymers on Morphology in Bicomponent Melt Spinning Fibers. Issue 4 (23rd September 2016) - Ayad, Esma; Cayla, Aurélie; Rault, François; Gonthier, Anne; Campagne, Christine; Devaux, Eric
Abstract: Bicomponent fibers were melt spun to investigate the effect of individual component viscosity on the cross section morphology. Two couples were tested, polypropylene MFI 18 (PP18 ) with polyamide 6 (PA6) and, polypropylene MFI 25 (PP25 ) with polyamide 6 (PA6). Viscosity versus shear rates was evaluated by both rotational and capillary rheometers to cover a large range of shear rates. Higher viscosity of PA6 compared to PP25 and PP18 at the theoretical shear rate resulted in the encapsulation of PA6 by PP25 and PP18 at the periphery of the bicomponent fiber cross section. Interfacial instability from the center to the periphery fiber was explained as a result of non‐uniformity of shear rates across the fiber cross section. Interface shape dependency on the viscosity ratio of the two polymers has been clearly demonstrated: lower viscosity component wrapping around the higher viscosity one whatever the initial configuration, that is, side‐by‐side or segmented pie structure.